THE ROLE OF MAGNESIUM AND THE IMPORTANCE OF HYPOMAGNESIEMIA IN HUMANS - Ana,; Milovanović, Srđan; Medić, Branislava; Savić Vujović, Katarina R (Medicinski podmladak, 2023)
Magnesium is the second most present cation in cells. The highest percentage of magnesium is found in bones (over 60%), slightly less in muscles and soft tissues. About 1% of magnesium is in circulation, present in three forms, of which the ionized one has the highest biological activity. Magnesium is active in almost every metabolic and biochemical process inside a cell. Magnesium homeostasis is essential for optimal function of an organism. Blood analysis is the simplest method of assessing magnesium status. Whole blood and its fractions (serum and plasma), as well as blood cells (erythrocytes, peripheral blood mononuclear cells and platelets) may be used to assess the content of magnesium in blood. The measurement of ionized magnesium is one of the latest and most precise methods since it assesses the status of the most biologically active form of magnesium. As the measurement is made from a peripheral blood sample, this method is relatively quick and simple which enables the rapid identification of persons with a deficiency of this important ion as well as the risk related to its deficiency.Magnesium deficiency can be caused by poor diet, hormonal imbalance, electrolyte imbalance and numerous other factors. In situations of gradual development of hypomagnesemia, even a severe deficit can pass without visible signs. In most cases, a lack of magnesium begins with complaints in the form of nausea and a feeling of fatigue. Magnesium deficiency is associated with cardiovascular diseases, metabolic syndrome and diabetes, fibromyalgia and almost all CNS diseases. Based on the relationships between certain deseases and magnesium deficiency identified so far, a rapid assessment of the status of this important divalent cation in an organism would allow a better  screening, more accurate diagnosis and faster recovery.
Keywords: magnesium; hypomagnesiemia; measurement; diseases